Pengaruh Motivasi dan Kepuasan Kerja terhadap Kinerja Pegawai dengan Kompensasi sebagai Variabel Intervening - Dasep Suryanto (Management Studies and Entrepreneurship Journal (MSEJ), 2020)
Performance refers to employee performance as measured by standards or criteria set by the company. Because the number of population in this study is not too much, then the technique of determining the sample is saturated sampling (census), where all members of the population are used as the research sample of 40 employees, all employees working in the North Payakumbuh District Head Office of Payakumbuh City consisting of men 18 people and 22 women. The data analysis technique used in this study is the SEM approach with PLS. From the results of the study concluded that work motivation directly has a positive and significant effect on the performance of Payakumbuh North Sub-District Office Employees, the variable of job satisfaction (KK) directly has a positive and not significant effect on the performance of Payakumbuh North Sub-District Office Employees, then indirectly work motivation has a positive and not significant effect on compensation Payakumbuh North Sub-district Payakumbuh Office Employees, while job satisfaction has a positive and significant effect on compensation Payakumbuh North Sub-District Payakumbuh Office Employee, compensation variable has a positive but not significant effect on the performance of Payakumbuh North Sub-district Payakumbuh Office Employee . Then the variable of work motivation and job satisfaction can be mediated by the compensation variable on the performance of North Payakumbuh District Office Employees Payakumbuh. Keywords: Motivation, Compensation, Satisfaction, Performance